PENGARUH STRUKTUR MODAL, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Pramesti, Lathifah Dwi; Arifah, Dista Amalia (Innovative: Journal Of Social Science Research, 2025)
The growth of business in Indonesia is evidenced by the rise in the number of businesses listed on the Indonesia Stock Exchange (IDX), going from 668 firms in December 2021 to 800 companies in August 2024. Intensifying rivalry necessitates that enterprises augment their firm worth while addressing stakeholder interests. This study seeks to examine the impact of capital structure, profitability, and business size on firm value. A quantitative methodology employing a causal-comparative design was utilized. The sample comprised 45 manufacturing firms in the industrial sector listed on the IDX from 2021 to 2024, selected by purposive selection methods. Financial records as secondary data were acquired from the official IDX website and examined by multiple linear regression. The findings indicated that capital structure, profitability, and firm size did not significantly impact firm value, implying that additional factors beyond the examined variables may exert a more substantial influence on firm value in this sector.